The Korean War : no victors, no vanquished - Sandler, Stanley, 1937- (Warfare and history., 1999)
An interpretative history of the Korean War within the context of Korea's history. The text assesses the role of North and South Korea and allied forces, and evaluates the contribution of UN naval forces and the impact on the homefront.